(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This study aimed to determine the prevalence of Giardia lamblia infection in Al-Najaf province, Iraq, based on various risk variables for sex years. From October 2015 to March 2021, samples were collected from suspected patients in the AL-Hakeem hospital and AL-Zahra maternity and paediatrics clinics in AL-Najaf province; stool samples were collected into clean, wide-mouth specimen bottles from suspected patients, and freshly voided stool specimens were processed and examined microscopically for intestinal paralysis. The current investigation found that 44 out of 44 (9.77%) patients were infected after detecting cyst and trophozoite of G. lamblia. The infection rate is proportional to the size of the family. Children from tiny families had the lowest infection rate (18.3%/15/82) and 18.3% (15/82). (4 persons). The infection rate gradually increased as family size grew, reaching 83.3 percent (5/6) in children from big households (12 persons). Based on the chi-square test, it was discovered that family size is non-significantly (P > 0.05) connected with pinworm infection.